The Effect of Compensation on Enhancing Employee Performance - Bachtiar Arif, Bachtiar; Romadhoni, Moh. Gufron; Tanjung, Rosdiana Imroati Kurnia; Wibowo, Teguh; Al-Amin, Al-Amin (Sharia Business Management Department of STEBIS Bina Mandiri, 2024)
This research was conducted with the main objective of identifying the influence of compensation on employee performance at PT Citra Sejati Lestarindo in Bekasi. The research method used is explanatory research, which aims to explain the cause-and-effect relationship between the compensation variable and employee performance. A sample of 68 respondents was taken from the company, using statistical analysis techniques such as regression, correlation, determination, and hypothesis testing. The results of this research show that the compensation variable, expressed in an average score of 3.74, falls within the